The use of citric acid and NPK fertilizer to enhance phytoextraction of nickel by Bajo starfruit plant (Sarcotheca celebica Veldk.) - Naima Haruna; Tatik Wardiyati; Moch Dawam Maghfoer (Brawijaya University, 2020)
Bajo starfruit is a wild plant that commonly grows in nickel mining areas and it is known to have the ability to take up Ni metal from the soil, even though its Ni uptake ability is still relatively low. The objective of this study was to explore the effect of the application of citric acid and NPK fertilizer on the ability of Bajo starfruit plant in phytoextraction of Ni from post nickel mining land. Citric acid as a ligand is expected to enhance the availability of Ni in the soil so that Ni uptake by plants increases, while NPK fertilizer is expected to enhance crop biomass production. The treatments tested were combinations of four doses of citric acid (0, 1, 2 and 3 g of citric acid/kg of soil) with two doses of NPK fertilizer (0, and 1.33 g/kg of soil). Eight treatments were arranged in a factorial randomized block design with four replications. The results showed that the application of NPK fertilizer without citric acid increased the number of leaves and dry weight of plants. After the growth of Bajo starfruit for 25 weeks, the application of 3 g citric acid/kg of soil without application of NPK fertilizer reduced the total soil Ni from 8926 ppm to 2400 ppm i.e.73.11%. Application of 2 g citric acid/kg of soil and 1.33 g NPK fertilizer/kg of soil resulted in Ni uptake by 118.18 mg/plant or increased by 38.61% compared to control. Application of 2 g citric acid/kg of soil without application of NPK fertilizer increased the BCF value of Bajo starfruit for nickel from 0.032 (control) to 0.035. However, treatments without the application of citric acid and fertilizer resulted in a higher TF value (13.9).